Integrating Digital Skills in Technical and Vocational Education: A Systematic Review in the Context of Industry 4.0 - Radita Kurnia; A. Muhammad Syafar; Edarho Oghenevwede Oyovwi (Academic Bright Collaboration, 2026)
Purpose - This study aims to systematically review how digital skills are integrated into TVET and identify the main strategies and contextual factors influencing their effectiveness. Methods - This study employed a systematic literature review using the PRISMA 2020 framework. Data were collected from the Scopus database, focusing on journal articles published between 2023 and 2025. A total of 34 studies were selected through rigorous screening and eligibility processes. Findings -The review identifies three main strategies for integrating digital skills in TVET: curriculum redesign aligned with Industry 4.0, the adoption of digital learning technologies, and innovative pedagogical models. Successful implementation is influenced by teachers’ digital competence, learner readiness, institutional infrastructure, and policy support. Research Implications - Digital skills integration in TVET is a multidimensional process requiring alignment between curriculum, pedagogy, institutional support, and workforce demands, providing an evidence-based foundation for developing adaptive and sustainable TVET systems in the digital age. Originality - This study provides a systematic and integrated synthesis of recent research (2023–2025) on digital skills integration in TVET by consolidating fragmented findings across curriculum, pedagogy, and institutional dimensions using the PRISMA 2020 framework.